Expression of SLCO transport genes in castration resistant prostate cancer and impact of genetic variation in SCLO1B3 and SLCO2B1 on prostate cancer outcomes - Wright, Jonathan L (2011)
BACKGROUND: Metastases from men with castration resistant prostate cancer (CRPC) harbor increased tumoral androgens vs. untreated prostate cancers (PCa). This may reflect steroid uptake by OATP/SLCO transporters. We evaluated SLCO gene expression in CRPC metastases and determined whether PCa outcomes are associated with single nucleotide polymorphisms (SNPs) in SLCO2B1 and SLCO1B3, transporters previously demonstrated to mediate androgen uptake. METHODS: Transcripts encoding 11 SLCO genes were analyzed in untreated PCa, and in metastatic CRPC tumors obtained by rapid autopsy. SNPs in SLCO2B1 and SLCO1B3 were genotyped in a population-based cohort of 1,309 Caucasian PCa patients. Median survival follow-up was 7.0 years (0.77–16.4). The risk of PCa recurrence/progression and PCa-specific mortality (PCSM) was estimated with Cox proportional hazards analysis. RESULTS: Six SLCO genes were highly expressed in CRPC metastases vs. untreated PCa, including SLCO1B3 (3.6 fold, p=0.0517) and SLCO2B1 (5.5 fold, p=0.0034). Carriers of the variant alleles SLCO2B1 SNP rs12422149 (HR 1.99, 95% CI 1.11 – 3.55) or SLCO1B3 SNP rs4149117 (HR 1.76, 95% CI 1.00 – 3.08) had an increased risk of PCSM. CONCLUSIONS: CRPC metastases demonstrate increased expression of SLCO genes vs. primary PCa. Genetic variants of SLCO1B3 and SLCO2B1 are associated with PCSM. Expression and genetic variation of SLCO genes which alter androgen uptake may be important in PCa outcomes. IMPACT: OATP/SLCO genes may be potential biomarkers for assessing risk of prostate cancer-specific mortality. Expression and genetic variation in these genes may allow stratification of patients to more aggressive hormonal therapy or earlier incorporation of non-hormonal based treatment strategies.